Penatalaksanaan Edukasi Tentang Gizi Balita Stunting di Wilayah Kerja Puskesmas Kopelma Darussalam Kota Banda Aceh - Futry Maysura; Noeroel Arham; Erna Safitri (Panggung Kebaikan : Jurnal Pengabdian Sosial, 2024)
Stunting is a condition of toddlers that has a negative impact on growth and development when compared to age. The incidence of stunting is a major nutritional problem facing Indonesia, and stunting is a topic that needs attention from all quarters given its impact. Lack of information about stunting can lead to quite a lot of misconceptions in the community, including the assumption that stunting is a normal condition for less height, even some parents do not know about stunting This study is a qualitative research. Initial informants were determined using purposive sampling technique. This study aims to help toddlers achieve optimal physical growth according to their age, improve cognitive development of toddlers through nutritious nutritional intake, and conduct early detection of stunting cases through regular growth monitoring at the puskesmas. There are five villages targeted by this program, namely ie masen kaye adang village with 13 stunting toddlers, lamgugob village with 6 toddlers, kopelma village with 12 toddlers, rukoh village with 20 toddlers, and dayah raya village with 17 toddlers. The implementation of the PMT program in August has been done carefully. One important preparation was the training given to cadres in each village. These cadres will be responsible for assisting in the implementation of the program, including in terms of preparing the food menu that will be given to stunted children.